PARENTING PATTERNS WITH GADGET ADDICTION IN SCHOOL AGE CHILDREN AT SDN 02 RENGEL - Savitri, ike Prita; Titik Sumiatin; su'udi (Prodi keperawatan sidoarjo, politeknik kesehatan kemenkes surabaya indonesia, 2023)
Parenting patterns of parents in educating and supervising children when using gadgets are important because in addition to having a positive impact, gadgets also have a negative impact on children. One of the negative impacts of using gadgets continuously and without restrictions from parents can lead to gadget addiction behavior in children. The purpose of this study was to determine the relationship between parenting and gadget addiction in school-age children at SDN 02 Rengel. The research design used is a correlation analytic survey with a cross sectional approach to students at SDN 02 Rengel in the 2021/2022 academic year. The sampling technique used is total sampling with a sample of 104 students. Data was collected by filling out a parenting style questionnaire and a validated gadget addiction questionnaire. The Spearmen test was conducted to determine the relationship between parenting patterns and gadget addiction. Based on the Spearman Correlation Test between parenting patterns and gadget addiction in school-age children at SDN 02 Rengel in the 2021/2022 academic year, a value of 0.09> from 0.05 means that there is no significant relationship between parenting patterns and gadget addiction. the correlation coefficient between parenting and gadget addiction is 0.163, meaning that there is a very weak relationship between parenting and gadget addiction in school-age children at SDN 02 Rengel.Parenting patterns are not the main cause of children being addicted to gadgets, but there are several other factors that can influence them, causing children to become addicted to heavy gadgets.